2021
DOI: 10.1002/nbm.4510
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease pathology is associated with earlier alterations to blood–brain barrier water permeability compared with healthy ageing in TgF344‐AD rats

Abstract: The effects of Alzheimer's disease (AD) and ageing on blood-brain barrier (BBB) breakdown are investigated in TgF344-AD and wild-type rats aged 13, 18 and 21 months. Permeability surface area products of the BBB to water (PS w ) and gadolinium-based contrast agent (PS g ) were measured in grey matter using multiflip angle multiecho dynamic contrast-enhanced MRI. At 13 months of age, there was no significant difference in PS w between TgF344-AD and wild-types (p = 0.82). Between 13 and 18 months, PS w increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Dickie et al reported that DCE-MRI failed to detect the difference between the TgF344 rats and wild-type rats at 18 months-of-age and that the increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type rats [ 245 ]. Using the same method, Dickie et al further showed in a cross-sectional study that BBB water permeability was affected earlier in TgF344 rats (13–18 months-of-age) compared to that in wild-type rats in normal ageing (18–21 months-of-age) [ 246 ]. Further studies are required to establish non-invasive imaging tools for visualizing BBB integrity and to elucidate the degree of BBB impairment in AD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Dickie et al reported that DCE-MRI failed to detect the difference between the TgF344 rats and wild-type rats at 18 months-of-age and that the increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type rats [ 245 ]. Using the same method, Dickie et al further showed in a cross-sectional study that BBB water permeability was affected earlier in TgF344 rats (13–18 months-of-age) compared to that in wild-type rats in normal ageing (18–21 months-of-age) [ 246 ]. Further studies are required to establish non-invasive imaging tools for visualizing BBB integrity and to elucidate the degree of BBB impairment in AD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently used this experimental approach to report WM k po decreases with HC aging 12 . Other investigators have reported BBB water permeability increases in rat brain Alzheimer's disease (AD) models 58,59 . Though the researchers used the same method as here, and measured the k po and v b factors separately, they report only the composite P w S products.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Other investigators have reported BBB water permeability increases in rat brain Alzheimer's disease (AD) models. 58 , 59 Though the researchers used the same method as here, and measured the k po and v b factors separately, they report only the composite P w S products. Thus, it is impossible to know if water permeation does actually increase in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Dickie et al reported that DCE-MRI did not detected the difference between the TgF344 and wild-type rats at 18 months-of-age, and that increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type [203]. Using the same method, Dickie et al further showed in a cross-sectional study that BBB water permeability is affected earlier in TgF344 rats (between 13-18 months-of-age) compared to that in wild-type mice in normal ageing (between 18-21 months-of-age) [204]. Further studies are required to further establish non-invasive imaging tools for visualizing BBB integrity and to elucidate the degree and role of BBB impairment in AD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[81] T2* Tg SwDI mice [145] T2*w APP23 mice [144] DCE 5×FAD, APOE mice [202] MFAME-DCE TgF344 rats [203,204] T2*w,…”
Section: Declaration Of Interestmentioning
confidence: 99%